2002
DOI: 10.1002/nau.10041
|View full text |Cite
|
Sign up to set email alerts
|

c‐Fos expression in the spinal cord after acute sacral segmental nerve stimulation

Abstract: SNS alone caused a near maximal response in c-Fos expression such that adding LUT irritation did not cause a linear increase in c-Fos. Subsequent LUT irritation could not induce additional expression of c-Fos within the spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…Immunoreactivity to c‐ fos protein (a neuronal proto‐oncogene) was assessed at each spinal level in four control rats, six rats that underwent electrode implantation and 2 h of SNS and six rats that underwent electrode implantation alone. The authors demonstrated that SNS increased the number of c‐ fos ‐positive cells in the L5 to S3 segments, primarily in L6 and S1 (the segments which innervate the anorectum in the rat) when compared to both the control and electrode implantation only group and also that c‐ fos immunoreactivity was increased in all four sections of the spinal cord (dorsal commissure, lateral and medial dorsal horns and sacral parasympathetic nucleus) …”
Section: Resultsmentioning
confidence: 99%
“…Immunoreactivity to c‐ fos protein (a neuronal proto‐oncogene) was assessed at each spinal level in four control rats, six rats that underwent electrode implantation and 2 h of SNS and six rats that underwent electrode implantation alone. The authors demonstrated that SNS increased the number of c‐ fos ‐positive cells in the L5 to S3 segments, primarily in L6 and S1 (the segments which innervate the anorectum in the rat) when compared to both the control and electrode implantation only group and also that c‐ fos immunoreactivity was increased in all four sections of the spinal cord (dorsal commissure, lateral and medial dorsal horns and sacral parasympathetic nucleus) …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, SNS is typically used for treating diseases of the pelvic organs (36,48). However, more studies indicate the underlying central mechanism of SNS (8,15,18,20). Until now, no animal studies explored upper gastrointestinal effects of SNS.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SNS increased the number of c-fospositive cells in the L 5 to S 3 spinal cord. Likewise, some studies indicated that neuromodulation of the sacral nerve might act on a central nerve system level (8,15,18,20). Therefore, some previous studies attempted to investigate the effects of SNS on upper gastrointestinal motor functions.…”
Section: Introductionmentioning
confidence: 99%
“…Este mensajero se expresa después de la presencia de algún factor irritante químico sobre la vejiga o el tracto urinario bajo. Esto demuestra que la neuromodulación actúa también a nivel de mensajeros (18)(19)(20).…”
Section: Discussionunclassified
“…La neuromodulación provocada mediante estímulo transcutáneo o percutáneo del tibial, tiene efectos en la vejiga mediante la vía del plexo sacro, a través de estimulación aferente retrógrada (20).…”
Section: Discussionunclassified